A self-assembling amphiphilic perylene bisimide and its application for WORM memory devices. (19th September 2016) - Li, Junfeng; Yang, Chenglong; Chen, Ying; Lai, Wen-Yong
Abstract : Morphologies of the amphiphilic perylene bisimide assemblies were controlled and switched by external stimuli to afford a good-performance WORM memory device. Abstract : Solvent-dependent self-assemblies of an amphiphilic molecule based on perylene bisimide were employed in the fabrication of well-defined millimeter long nanorods and high density nanofibers, respectively. Moreover, the fabricated memory device demonstrated good behaviours with a low operating voltage, high ON/OFF ratio, long retention time, and good stability.